2014
DOI: 10.1111/jre.12226
|View full text |Cite
|
Sign up to set email alerts
|

Brain‐derived neurotrophic factor prevents the endothelial barrier dysfunction induced by interleukin‐1β and tumor necrosis factor‐α

Abstract: BDNF played an important role in inhibiting endothelial barrier dysfunction, which suggests that it may assist in enhancing periodontal tissue regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 61 publications
(90 reference statements)
0
9
0
Order By: Relevance
“…An in vitro study indicated that the addition of BDNF could attenuate apoptosis induced by TNF-α and IFN-γ in enteric glial cells (EGCs) (Steinkamp et al 2012). In human vascular endothelial cells, BDNF maintains the integrity of blood vessel walls and avoids vascular leakage by protecting cells from apoptosis in response to inflammatory mediators (Matsuda et al 2015, Takeda et al 2013). In addition, BDNF is highly expressed in colorectal cancer compared with non-tumor tissues, and increased expression of BDNF can inhibit spontaneous cell apoptosis in tumorigenesis (Brunetto de Farias et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…An in vitro study indicated that the addition of BDNF could attenuate apoptosis induced by TNF-α and IFN-γ in enteric glial cells (EGCs) (Steinkamp et al 2012). In human vascular endothelial cells, BDNF maintains the integrity of blood vessel walls and avoids vascular leakage by protecting cells from apoptosis in response to inflammatory mediators (Matsuda et al 2015, Takeda et al 2013). In addition, BDNF is highly expressed in colorectal cancer compared with non-tumor tissues, and increased expression of BDNF can inhibit spontaneous cell apoptosis in tumorigenesis (Brunetto de Farias et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…21 BDNF modulates cadherin expression and shedding 30,31 and interacts with tumor necrosis factor-α. 32,33 Both cadherin 34 and tumor necrosis-α 35-37 contribute to atrial structural remodeling in human and animal studies, and therefore changes in BDNF may promote development of a substrate vulnerable to AF. We hypothesized that BDNF is associated with incident AF, possibly through modulation of endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Studies report that in human minor salivary glands, as claudin‐1 and claudin‐4 increase, ZO‐1 and occludin decrease [11]. Additionally, the expression of the epithelial tight junction proteins ZO‐1, occludin, claudin‐1 and claudin‐2 can be regulated by brain‐derived neurotrophic factor (BDNF) [12]. BDNF, a member of the neurotrophin polypeptide family, is abundantly and widely expressed in the nervous system [13].…”
Section: Introductionmentioning
confidence: 99%